Disposal of waste computer hard disk drive: data destruction and resources recycling. Issue 6 (June 2013) - Yan, Guoqing; Xue, Mianqiang; Xu, Zhenming
An increasing quantity of discarded computers is accompanied by a sharp increase in the number of hard disk drives to be eliminated. A waste hard disk drive is a special form of waste electrical and electronic equipment because it holds large amounts of information that is closely connected with its user. Therefore, the treatment of waste hard disk drives is an urgent issue in terms of data security, environmental protection and sustainable development. In the present study the degaussing method was adopted to destroy the residual data on the waste hard disk drives and the housing of the disks was used as an example to explore the coating removal process, which is the most important pretreatment for aluminium alloy recycling. The key operation points of the degaussing determined were: (1) keep the platter plate parallel with the magnetic field direction; and (2) the enlargement of magnetic field intensity B and action time t can lead to a significant upgrade in the degaussing effect. The coating removal experiment indicated that heating the waste hard disk drives housing at a temperature of 400 °C for 24 min was the optimum condition. A novel integrated technique for the treatment of waste hard disk drives is proposed herein. This technique offers the possibility of destroying residual data, recycling the recovered resources and disposing of the disks in an environmentally friendly manner.